The in vitro antiviral activity of Lacticaseibacillus casei MCJ protein-based metabolites on bovine viral diarrhea virus. Issue 2 (3rd April 2023) - Bhuyan, Anjuman Ara; Akbar Bhuiyan, Ali; Memon, Atta Muhammad; Zhang, Bingzhou; Alam, Jahangir; He, Qi-Gai
Abstract: Bovine viral diarrhea virus (BVDV) is a ubiquitous immunosuppressive etiological agent which is economically important for a wide host range in the livestock industry. Lactobacillus spp. has widely been using in the field of management and treatment of gastro-enteric disease for both humans and animals. The ability of Lacticaseibacillus casei MCJ protein-based metabolized to suppress BVDV infection in Madin–Darby Bovine Kidney cell line was demonstrated in this study. The protein-based metabolites were extracted from the cultured L. casei to obtain the safest and beneficial form of the probiotic bacteria. It is revealed that LPM have no cytotoxic effect and the cell viability remain more than 80% even after the cells are treated with 3000 µg/mL of LPM. The results of the plaque formation assay showed that LPM can reduce the viral infection rate. To know the mechanism of LPM for anti-BVDV activity, MDBK cells were exposed to LPM before, after and co-incubation of virus infection. The co-treatment of LPM with BVDV revealed the best results. The results suggest that the LPM has a potential anti-BVDV activity which could be a prospective candidate for the prevention and control of BVDV infection in an animal.